Automatic Measurement of Eye Features Using Image Processing - Morimoto, Carlos Hitoshi (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2009: Anais do IX Workshop de Informática Médica, 2009)
This paper presents a camera based eye anthropometric measurement system that automatically computes the pupil size, the inter-pupillary distance, palpebral fissure (PF) and the marginal reflex distance (MRD). These values are in general manually obtained in ophthalmologic exams using a millimetric ruler or gauges, and therefore are subject to errors. Besides improving the accuracy and reliability of the measurements, the system uses near-infrared (NIR) light that allows its use in different lighting conditions. A single NIR non-calibrated camera is used to measure both eyes at the same time. The eye features are extracted using image processing algorithms, and metric values are computed using a known chessboard pattern as reference. Experimental results demonstrate the real-time performance, accuracy and robustness of the method.